Contemplation of the human condition through the embodiment of anthropomorphic sociable objects. - Teo, Kok Yung. (2012)
Product/industrial design has been related to the advancement of modern lifestyle and the phrase “standard of living”. In the 21st century, technology have brought about countless products and material goods to the mass consumers, the search for better products leads to interaction design and sociable products, this project focuses on the area of development in sociable robots. A collection of dismembered anthropomorphic objects is designed for the common urban dweller, in a satirical way to improve the user’s standard of living. It proposes an alternative to the highly anthropomorphic domestic servant robots, questioning the needs and desire of mimicking humans. Juxtaposing the embodiment of mechanical objects against the human entity, this project seeks to provoke contemplation on the human condition.